Three new species of Hyposmocoma (Lepidoptera, Cosmopterigidae) from the Hawaiian Islands, based on morphological and molecular evidence - Schmitz, Patrick; Rubinoff, Daniel (Zootaxa, 2008)
The Cosmopterigid genus Hyposmocoma (Lepidoptera, Cosmopterigidae) is endemic to Hawaii and contains over 350 recognized species, though only one new species has been described in the past 62 years. We describe and illustrate three new species of Hyposmocoma: Hyposmocoma kaupo sp. nov. from the island of Maui, H. kapakai sp. nov. from Oahu, and H. kaikuono sp. nov. from Molokai, all known from both sexes, and all apparently single-island endemics. The casemaking larvae of all three species feed on lichen and organic debris on dry rocks in open or partly forested habitat. While morphological differences among these three species are small, genetic divergence across parts of the mitochondrial gene cytochrome oxidase I and the nuclear genes elongation factor 1 indicate universally deep divergence, making these taxa a classic example of sibling species.